Pengembangan Media Interactive Assisted Learning (IVAL) dalam Mata Kuliah Asesmen untuk Mahasiswa Tunagrahita Ringan - Badroeni -; Erik Wahyudin; Sofhian Fajrin Nasrulloh; Rela Imanulhaq (NUANSA INFORMATIKA, 2024)
The development of an innovative interactive assisted learning (IVAL) model for mildly mentally retarded students is an effort to create solutions related to the need for digital-based media to stimulate mildly mentally retarded students in assisting the learning process, in this context, in early childhood learning assessment courses at the PG-PAUD STKIP Muhammadiyah Kuningan. In fact, it has not used digital media to help students with special needs due to limited innovation of digital-based media. Through the research and development process carried out, the results of this research creates an android application entitled "Interactive Assisted Learning (IVAL) which is suitable to be applied as a learning medium for students with special needs and mild mental retardation to stimulate students in receiving, processing and storing information in brain memory. The feasibility of IVAL media is proven from the validation results of software engineering experts 73.3%, media experts 80.8% and PAUD lecturer practitioners 71.4%. The evidence of effectiveness is proven from the results of trials in the PG-PAUD Study Program which shows that the ability of students with special needs mild mental retardation is up to 90.3% with a gain score of 0.70 in the medium category and in class of assessment subjects, it is increased to 90.1% with a gain score of 0.70 in the medium category.